Conflicts associated with migratory processes: a political perspective - Sagitova, Victoria Ravilꞌevna; Ivanov, Andrey Valeryevich (Cuestiones Políticas, 2020)
The objective of the research was to discuss the conflictive nature of the migratory processes that occur in the world today. The need to adapt and solve daily problems inevitably requires the State to implement international, state and regional standards for the implementation of the rights and opportunities of migrants both in the territory of the donor country and in the territory of the recipient country. On the other hand, we see an increase in the phobia of migrants and the characteristic racism of countries where labor migration flows are increasing. In methodological terms, use was made of hermeneutics close to political ethnography. It is concluded that, for a long time, the criticism of racism has developed as a criticism of colonialism, Nazism, including anti-Semitism, and in modern times as a political criticism of migration-phobia and nationalism, in which the Racist speech and practices have found and do find obvious and complete expression. Migrant phobia is a concept that latently generates motives of political, ideological, racial, national, religious hatred, xenophobia, or hostility towards an ethnic or social group within the framework of social practices.